Electromagnetic band gap (EBG) for microstrip antenna design - Mohd. Isa, Ainor Khaliah (2007)
Microstrip patch antennas became very popular in mobile and radio wireless communication. This is because of ease of analysis and fabrication, and their attractive radiation characteristics. However, they have some drawbacks of low efficiency, narrow bandwidth and surface wave losses. In order to overcome the limitations of microstrip antennas such as narrow bandwidth (< 5%), lower gain (-6 dB), excitation of surface waves etc, a new solution method; using electromagnetic bandgap (EBG) materials, as substrates has attracted increasing attention. Unlike other methods, this new method utilizes the inherent properties of dielectric materials to enhance microstrip antenna performance. These periodic structures have the unique property of preventing the propagation of electromagnetic waves for specific frequencies and directions which are defined by the shape, size, symmetry, and the material used in their construction. Some EBG structures include drilled holes in dielectrics, patterns etched in the ground plane, and metallic patches placed around microstrip structures. The aim of this project are to design, simulate and fabricate the new EBG structure operating at 2.4GHz frequency and study the performance of the rectangular microstrip antenna with and without EBG structure. Those designs were simulated with Microwave Office software and tested with the Network Analyzer. Both, simulated and measured data were compared and contrasted.